Employee Performance Measurement Using the Human Resource Scorecard Method - Besse Faradiba; Indrayani; Qarina (LPPM Undiksha, 2025)
In the era of globalization and increasing business competition, measuring the effectiveness of human resource management has become critically important. This study aims to provide a more objective assessment of employee performance by incorporating multiple perspectives, including internal business processes, customer satisfaction, and organizational learning, which ultimately supports BMT Al-Birry in addressing organizational challenges and enhancing its competitiveness. This research employs a quantitative approach using the Human Resources Balanced Scorecard (HR-BSC) framework. The research subjects consist of 15 employees who have been employed for a minimum of three years. Primary data were collected through Likert-scale questionnaires and interviews, while secondary data were obtained from online sources, academic journals, and internal documents of BMT Al-Birry. The collected data were analyzed using regression analysis models. The findings indicate that the financial perspective of the Human Resources Balanced Scorecard at Baitul Maal Wat Tamwil Al-Birry, measured through return on assets, profit margin, and operating ratio, demonstrates strong financial performance. Non-financial dimensions of the HR-BSC were assessed from the customer perspective, showing increased sales over the past three years. From the internal business process perspective, performance outcomes were classified as achieving high-quality results. This study implies that the implementation of the Human Resources Balanced Scorecard contributes to the alignment of human resource strategy with business strategy, enhances performance accountability, and strengthens an outcome-oriented organizational culture.